PENGARUH PEMBERIAN EKSTRAK BUAH MAJA (Aegle marmelos) TERHADAP MORTALITAS HAMA KEONG MAS (Pomacea canaliculata L.) PADA TANAMAN PADI VARIETAS INPARI 32 - Lalu Llham Suhendra; Cokorda Javandira; Eka Pasmidi Ariati; Dewa Nyoman Raka (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
The Effect of Maja Fruit (Aegle marmelos) on Mortality of Pests of Mas Conch (Pomacea canaliculata L.) on Rice Plants inpari variety 32 The golden snail (Pomaceae canaliculata L.) is one of the important pests of rice plants. This pest attack can cause yield loss of 40% - 70% in agricultural crops. This pest also has a wide spread rate in various regions in Indonesia. The control of the golden snail in this study uses maja fruit extract which contains chemical compounds Alkaloids, saponins and tannins that are toxic to pests. This research was carried out starting from August 4 to Septmbr 3, 2021. This study aimed to determine the effect of maja fruit extract on the mortality of the golden snail (Pomaceae canaliculata L.) pest on rice plants. The experimental design used was RAK with 6 treatment concentrations, namely control, 10ml, 20ml, 30ml, 40ml, 50ml. maja fruit extract and repeated 4 times. Observations show that the higher the concentration used, the higher the content of toxic compounds that can lead to higher mortality in gold snails. The highest gold snail mortality was at a concentration of 50 ml, the lower the concentration used, the higher the percentage of damage to rice plants. The highest percentage of damage to rice plants was in the 0 treatment with a percentage of 100%.